Creepy Crawlers: Animality and Ghost-humanism in Horror - Sethabutr, Proud (Journal of Ecohumanism, 2024)
Posthumanism has largely focused on non-human entities in the effort to decentralize the human. Ghosts, meanwhile, have been read symptomatically as codification of various social and, more recently, ecological anxieties. This paper interrogates how the ubiquitous horror trope of the crawling woman does more than signify. With Derrida’s The Animal that Therefore I Am as an intertext, this paper takes an ontological and phenomenological approach to the crawling woman and proposes a ghost-humanist reading of this figure as boundary-breaching in more ways that the physical.